The effects of nonwork and personal resources on frontline bank employees' work engagement and critical job outcomes - Karatepe, Osman M.; Ozturk, Anastasia; Kim, Taegoo Terry (Emerald Group Publishing Ltd, 2019)
Purpose - The purpose of this paper is to propose a research model that investigates work engagement as a mediator of the effect of family support on proclivity to leave work early, in-role performance (IRP), service recovery performance (SRP) and extra-role performance (ERP). The research model also examines work engagement as a mediator of the impact of self-efficacy on the aforesaid outcomes. In addition to these relationships, the study assesses self-efficacy as an underlying mechanism linking family support to work engagement. Design/methodology/approach - The authors employed a time-lagged design. Specifically, data were obtained from frontline bank employees (FBEs) in Russia in three waves, within one week time intervals. FBEs' performance outcomes were rated by their managers. Findings - As hypothesized, self-efficacy and family support foster FBEs' work engagement, which in turn reduces proclivity to leave work early and activates IRP, SRP and ERP. In line with the study predictions, the findings highlight the impact of self-efficacy in the intermediate linkage between family support and work engagement. Practical implications - Management should organize workshops where FBEs' family members are invited to participate. In such workshops, they can understand the nature of frontline service jobs in the competitive banking environment and are expected to provide support to FBEs. This is significant because family support influences work engagement directly and indirectly through self-efficacy and affects the above-mentioned performance outcomes only via work engagement. Training programs should not only focus on the development of knowledge, skills and abilities for service delivery and complaint handling but also center on the costs arising from nonattendance behaviors/intentions. As a result, these programs should make FBEs minimize such intentions. Originality/value - Work engagement is still a timely topic and there have been calls for the identification of factors influencing work engagement and its consequences among frontline employees. Therefore, our study uses family support and self-efficacy as the two crucial resources that can influence employees' positive psychological states and their work performance. Further, using solid theoretical underpinnings such as conservation of resources, social information processing, and job demands-resources theories, our study is the first to link family support and self-efficacy to multiple performance outcomes and nonattendance intentions via work engagement among FBEs.
Keywords: In-role performance; Work engagement; Self-efficacy; Bank employees; Family support; Nonattendance intentions